New Developments and Testing of Phase Change Materials to Optimize Thermal Efficiency on Power Cables for Different Load Scenarios - Ariana Ofélia Figueiredo Moreira Martins (2017)
The purpose of this research is to study and develop new methodologies related to the incorporation of phase change materials on power cables in order to improve their thermal efficiency and, as a consequence, enhance transmission reliability. According to specific load scenarios, the application of phase change materials on power cables could represent a significant impact in power system performance and equipment life-time.